Translation Quality of English - Javanese Songs By Pentul Kustik Band - Wardani, Intan Kusuma; Yuliasri, Issy (English Education Journal, 2020)
Translating English songs into Javanese language both semantically and emotionally presents a challenge to translators because regional differences always limits some linguistic and cultural aspects. Here, Pentul Kustik band attempts to provide a good English-Javanese song translation that can help Javanese people to understand the song and popularize it. Low’s Pentathlon Approach (2005) highlights several unique aspects of translating lyrics, which cover the elements of singability, sense, naturalness, rhythm, and rhyme. This study uses Low’s theory and assesses the quality of English-Javanese translation of song lyrics The object of this study is 15 English-Javanese song translation by Pentul Kustik Band. There are 328 data analyzed. The result shows that 223 data (68.09%) are considered singable and 105 data (32.02%) are considered less singable. In the aspect of sense, 142 data(46.30%) were considered having less accurate sense, while 186% data (53.70%) having accurate sense. In addition, 252 data (78.02%) are found to be natural and only 71 data (22.08%) are said to be less natural. The rhythm analysis indicates 123 data (37.50%) uses addition, 115 data (35.06%) uses reduction and 90 data(27.44%) preserves the original syllable numbers. The rhymes found in this study have 3 patterns. First, the translator replicates the sound and the pattern of the original song rhyme into the translated version. Second, the translator preserves the pattern of the original rhyme but modifies the sound used in the translated version. Third, some translations are found as half-rhymed or unrhymed free verses.